Characterization of Doubled Haploid Eggplant (Solanum melongena L.) Lines Obtained from Anther Culture - Rifa Kamalia Shinta Abdullah; Bambang Sapta Purwoko; Awang Maharijaya; Samsul Ma’arif; Iswari Saraswati Dewi (Journal of Tropical Crop Science, 2026)
Eggplant (Solanum melongena L.) is an important horticultural crop widely cultivated worldwide. Stable genetic material and comprehensive information on genetic variability are essential for the development of superior varieties. Previous studies have obtained genetically stable doubled-haploid (DH) lines through anther culture. However, their agronomic performance has not been well identified. Therefore, this study aims to characterize doubled haploid (DH) eggplant lines (Solanum melongena L.) and identify potential candidates for future use as parental lines in hybrid breeding programs. Eleven doubled-haploid lines and three commercial varieties were evaluated using a randomized complete block design. Quantitative data were analyzed using analysis of variance (ANOVA), followed by Tukey’s HSD test at a 5% significance level, and cluster analysis based on phenotypic similarity. The results revealed significant variability among the genotypes for all quantitative characters except days to final harvest. Cluster analysis classified the genotypes into two major groups. Among the evaluated genotypes, Pro-AM1, Pro-AM38, Pro- AM50, and Hit-AM30 exhibited superior yield-related characters and are considered promising parental lines for hybrid development in eggplant. These findings demonstrate substantial genetic variability among the double-haploid eggplant lines and provide valuable resources for selecting superior lines to support future hybrid development.